A behavioral screen for isolating zebrafish mutants with visual system defects. - Brockerhoff, S E (1995)
Optokinetic and phototactic behaviors of zebrafish larvae were examined for their usefulness in screening for recessive defects in the visual system. The optokinetic response can be reliably and rapidly detected in 5-day larvae, whereas the phototactic response of larvae is variable and not robust enough to be useful for screening. We therefore measured optokinetic responses of mutagenized larvae as a genetic screen for visual system defects. Third-generation larvae, representing 266 mutagenized genomes, were examined for abnormal optokinetic responses. Eighteen optokinetic-defective mutants were identified and two mutants that did not show obvious morphological defects, no optokinetic response a (noa) and partial optokinetic response a (poa), were studied further. We recorded the electroretinogram (ERG) to determine whether these two mutations affect the retina. The b-wave of noa larvae was grossly abnormal, being delayed in onset and significantly reduced in amplitude. In contrast, the ERG waveform of poa larvae was normal, although the b-wave was reduced in amplitude in bright light. Histologically, the retinas of noa and poa larvae appeared normal. We conclude that noa larvae have a functional defect in the outer retina, whereas the outer retina of poa larvae is likely to be normal.